2010
DOI: 10.1111/j.1865-1682.2010.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Pox outbreaks in Sheep and Goats at Makhdoom (Uttar Pradesh), India: Evidence of Sheeppox Virus Infection in Goats

Abstract: Sheeppox and goatpox outbreaks occur often in India incurring huge economic loss to the small ruminant industry. This paper describes two sheeppox outbreaks, of which one occurred in an organized sheep breeding farm at Makhdoom (Uttar Pradesh), India, during 2007 and another in goats at the Central Institute of Research on Goats, Makhdoom (Uttar Pradesh), India during 2008. In the first outbreak, a local Muzaffarnagari sheep breed was affected (n=477) with morbidity and mortality rates, respectively, of 100% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 16 publications
3
41
0
Order By: Relevance
“…However, recent records have indicated that some CaPV strains infect both sheep and goats (Bhanuprakash et al, 2006(Bhanuprakash et al, , 2010. Information based only on the host animal species from which the strain was first isolated is inadequate to identify CaPVs, and owing to the very close antigenic relationship among CaPVs, conventional serological methods cannot distinguish SPPV and GTPV.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent records have indicated that some CaPV strains infect both sheep and goats (Bhanuprakash et al, 2006(Bhanuprakash et al, , 2010. Information based only on the host animal species from which the strain was first isolated is inadequate to identify CaPVs, and owing to the very close antigenic relationship among CaPVs, conventional serological methods cannot distinguish SPPV and GTPV.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in young animals can exceed 50% but in naïve animals can reach 100% (Bhanuprakash et al, 2006). Capripoxviruses (CaPVs) are mainly host-specific, means that SPPV only infected sheep while GTPV only infected goats, but some recent researchers recorded that some strains of SPPV and GTPV could infect both sheep and goats (Bhanuprakash et al, 2006;Bhanuprakash et al, 2010). Conventional serological assays could not distinguish SPPV, GTPV and LSDV due to the close antigenic and virulence relationship (Balinsky et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The sheeppox and goatpox diseases are notifiable to Office Internationale des Epizooties (OIE) due to its economic impact. In India, sheeppox and goatpox diseases are endemic, which are host specific and pose a serious economic loss to small ruminant husbandry (Bhanuprakash et al, 2006;Bhanuprakash et al, 2010;Bhanuprakash et al, 2011). Although, SPPV and GTPV are considered as host-specific they can cross the species barrier i.e.…”
Section: Sheeppox and Goatpoxmentioning
confidence: 99%